HOW INNOVATION REQUIREMENTS, PRODUCT CREATIVITY, EMPLOYEE INGENUITY, AND DIGITAL CHANGE SHAPE STRATEGIC ORIENTATION - Yerkin, Nazarbay (Farabi Journal of Social Sciences, 2025)
Purpose. This study investigates the influence of innovation-related factors on strategic orientation in contemporary organizations. Specifically, it examines the impact of four variables: Innovativeness as a Job Requirement, Product Innovation, Employee Innovativeness, and Digital Transformation. Design/methodology/approach. A quantitative approach was adopted using a structured survey distributed via social networks (Instagram, Telegram, WhatsApp) through Google Forms. The survey gathered responses from 69 participants of diverse gender, age, and education levels within Kazakhstan. Regression analysis was employed to assess the relationships between the variables. Findings. The results indicate that Employee Innovativeness and Digital Transformation significantly influence Strategic Orientation, explaining 77% of its variance. In contrast, Innovativeness as a Job Requirement and Product Innovation showed no significant impact. The findings suggest that innovation embedded in organizational culture and supported by digital processes contributes more meaningfully to strategic adaptability than product-based innovation alone. Originality. This study contributes to the growing body of literature on strategic orientation by highlighting the comparative influence of internal innovation-related factors. It emphasizes the critical role of employee-driven innovation and digital transformation in shaping effective strategic frameworks. The research also points out limitations in existing models by showing that certain innovation indicators may not always predict strategic orientation in specific contexts. Recommendations for future research include using longitudinal designs and expanding geographic and industry scope to validate and generalize findings. Key words: strategic orientation, employee innovativeness, digital transformation, product innovation, job innovativeness